Collapsin response mediator protein 5-associated optic neuropathy: clinical characteristics, radiologic clues, and outcomes - Yan, Rong; Mao, Yu; Zeng, Huiyang; Liu, Qian; Jiang, Hanqiu; Peng, Jingting; Yang, Qingling; Cui, Shilei; Liu, Lei; Guo, Yanjun; Wang, Jiawei (Frontiers in Neurology, 2023)
Objective Collapsin response mediator protein 5-associated optic neuropathy (CRMP5-ON) is a rare entity of autoimmune optic neuropathy. This study aimed to review the neuro-ophthalmic findings and outcomes in a series of patients with CRMP5-ON to further characterize its clinical phenotype, radiologic clues, and outcomes. Methods This was a retrospective case series and a single-center medical chart review of all patients with CRPM5-seropositive ON at the Department of Neurology, Beijing Tongren Hospital, from December 1, 2020, to March 31, 2023. The main outcome measures were neuro-ophthalmic manifestations, radiologic characteristics, and clinical outcomes of CRMP5-ON; coexisting neural autoantibody, paraneoplastic associations, and the impact of immunosuppressant therapy. Results Five patients were identified. Four (80%) were female, and the average age at onset was 59.4 years (range 53–69 years), with an average follow-up of 15.3 months (range 1.4–28.7 months). The average best-corrected visual acuity (BCVA) at nadir was 20/120 (range 20/20 to count fingers). Seven of ten affected eyes (70%) showed diffuse defects of the central field. Painless bilateral involvement and optic disk edema occurred in 100% of patients, combined with vitritis, uveitis, or retinitis in four (80%). Four patients (80%) had MRI abnormalities along the optic nerve (one patient with optic nerve enhancement and three patients had optic nerve sheath enhancement or peribulbar fat enhancement). Three patients (60%) had optic neuropathy with other neurologic symptoms. Four patients (80%) had confirmed cancer (two were small-cell lung carcinoma, one was papillary thyroid carcinoma and another was thymoma and invasive pulmonary adenocarcinoma). All cancers were identified after the presentation of the optic neuropathy. The intervention included IVIG, IVMP, surgery and chemotherapy. The average BCVA at the last follow-up was 20/50 (range 20/20 to count fingers). Three patients had surgery during the initial hospitalization, and were stable during the follow-up. Among two patients who received IVMP, both had improvement after treatment, although one patient had worsening non-ocular neurologic symptoms during the steroid taper. Conclusion CRMP5-ON presented with optic disc edema, often bilateral involved and combined with vitreitis, retinitis, or uveitis. CRMP5-ON can present with MRI optic nerve or perineural optic nerve enhancement, especially in the optic nerve sheath. CRMP5-ON is closely related to paraneoplastic neurologic syndrome. Cancer screening and intervention are crucial to prognosis.